2016
DOI: 10.1051/matecconf/20167708006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dental Implant-abutment Interfaces on the Reliability of Implant Systems

Abstract: Abstract. In this paper, by analyzing the effects of two different kinds of implant-abutment connection interfaces under the same working condition on the mechanical and fatigue performances of the implant system as well as on the surrounding bones, we intend to study such effects on the reliability of the implants and provide a theoretical basis for the design and clinical application of dental implant systems. For the purpose, we adopt a 3-D modeling method to establish the model, and use FEA (finite element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Through the summary of implant cases [9] , it was found that for the implant site, the reason of missing teeth, bone quality, implant diameter, length, and material all affect the success of implant restoration. Li X [10] compared the implant stresses in the maxillary posterior region with different angles by FEA, and found that the Von-Mises stresses in the bone around the tilted implant were the ISSN 2616-5791 Vol.4, Issue 8: 65-70, DOI: 10.25236/AJMHS.2023.040811…”
Section: Implant Restoration For Single Missing Toothmentioning
confidence: 99%
“…Through the summary of implant cases [9] , it was found that for the implant site, the reason of missing teeth, bone quality, implant diameter, length, and material all affect the success of implant restoration. Li X [10] compared the implant stresses in the maxillary posterior region with different angles by FEA, and found that the Von-Mises stresses in the bone around the tilted implant were the ISSN 2616-5791 Vol.4, Issue 8: 65-70, DOI: 10.25236/AJMHS.2023.040811…”
Section: Implant Restoration For Single Missing Toothmentioning
confidence: 99%